Fusobacterium nucleatum Subspecies Differ in Biofilm Forming Ability in vitro - Muchova, Maria; Balacco, Dario L.; Grant, Melissa M.; Chapple, Iain L. C.; Kuehne, Sarah A.; Hirschfeld, Josefine (Frontiers in Oral Health, 2022)
Development of dysbiosis in complex multispecies bacterial biofilms forming on teeth, known as dental plaque, is one of the factors causing periodontitis. Fusobacterium nucleatum (F. nucleatum) is recognised as a key microorganism in subgingival dental plaque, and is linked to periodontitis as well as colorectal cancer and systemic diseases. Five subspecies of F. nucleatum have been identified: animalis, fusiforme, nucleatum, polymorphum and vincentii. Differential integration of subspecies into multispecies biofilm models has been reported, however, biofilm forming ability of individual F. nucleatum subspecies is largely unknown. The aim of this study was to determine the single-subspecies biofilm forming abilities of F. nucleatum ATCC type strains. Static single subspecies F. nucleatum biofilms were grown anaerobically for three days on untreated or surface-modified (sandblasting, artificial saliva, fibronectin, gelatin or poly-L-lysine coating) plastic and glass coverslips. Biofilm mass was quantified using crystal violet (CV) staining. Biofilm architecture and thickness were analyzed by scanning electron microscopy and confocal laser scanning microscopy. Bioinformatic analysis was performed to identify orthologs of known adhesion proteins in F. nucleatum subspecies. Surface type and treatment significantly influenced single-subspecies biofilm formation. Biofilm formation was overall highest on poly-L-lysine coated surfaces and sandblasted glass surfaces. Biofilm thickness and stability, as well as architecture, varied amongst the subspecies. Interestingly, F. nucleatum ssp. polymorphum did not form a detectable, continuous layer of biofilm on any of the tested substrates. Consistent with limited biofilm forming ability in vitro, F. nucleatum ssp. polymorphum showed the least conservation of the adhesion proteins CmpA and Fap2 in silico. Here, we show that biofilm formation by F. nucleatum in vitro is subspecies- and substrate-specific. Additionally, F. nucleatum spp. polymorphum does not appear to form stable single-subspecies continuous layers of biofilm in vitro. Understanding the differences in F. nucleatum single-subspecies biofilm formation may shed light on multi-species biofilm formation mechanisms and may reveal new virulence factors as novel therapeutic targets for prevention and treatment of F. nucleatum-mediated infections and diseases.